Financial Performance Analysis: Profitability, Liquidity, and Solvency Ratios in Indonesian Property Sector Companies - Aurelia Widya Astuti; Muhamad Zaenal Asikin (Politeknik Siber Cerdika Internasional, 2026)
The property sector in Indonesia faces complex financial challenges, including the need to simultaneously manage profitability, liquidity, and solvency under conditions of post-pandemic economic recovery and high capital dependency. Despite the sector’s strategic role in the national economy, empirical studies that comprehensively assess financial performance across multiple ratio dimensions within a single analytical framework remain limited. This study aims to analyze the financial performance of PT XYZ Tbk, an Indonesian property sector company listed on the Indonesia Stock Exchange (IDX), through a multidimensional financial ratio analysis encompassing four dimensions: profitability, liquidity and solvency, operational efficiency, and managerial policy. A descriptive quantitative approach was employed using secondary data drawn from the company’s audited financial statements for the first quarter of 2025 (January–March 2025), with comparative data from the first quarter of 2024, both obtained from the IDX official platform. Sixteen financial ratio indicators were calculated and interpreted against recognized industry benchmarks. The results reveal a critical disparity between the Gross Profit Margin (GPM 21.71%) and net-profit-based indicators (NPM 0.0231%; ROA 0.0002%; ROE 0.0006%), indicating severe compression of bottom-line profitability driven by non-operating expenses under high leverage conditions (DER 1.6354). Although the Current Ratio (1.4423) appears nominally adequate, the very low Quick Ratio (0.0994) exposes a hidden liquidity risk attributable to inventory dominance (93.1% of current assets). Operational efficiency indicators further reflect structural weaknesses, with Asset Turnover recorded at only 0.0102 times and Inventory Turnover at 0.0162 times. On the managerial policy dimension, sales declined by 13.98% and net profit contracted by 99.77% year-on-year, signaling acute multidimensional financial pressures. These findings imply that property sector companies must adopt more balanced and adaptive financial management strategies—particularly in optimizing capital structure, accelerating inventory conversion, and strengthening operating cash flow—to sustain long-term performance stability and competitiveness.